Platformed Ritual in Emotions: (Dys)functional Construction of Intimacy in Digital Dating in China - Xiyu Cao; Ping Sun (Social Media + Society)
Previous studies have discussed digital dating by the “love-is-fast” metaphor and the successful and failed stories on dating platforms to debate the ideal of modern intimacy; however, the conceptualization of rituals and mechanisms for constructing intimacy in a continuum of online and offline everyday life has been left unstudied. Drawing on Eva Illouz’s argument on a regime of performativity of emotions and ritual scholarship, this study investigates the staged (dys)functioning of platform-constructed acts. Based on 35 interviews and 14-month user-led cross-platform walkthroughs, this study examines how users deployed and interpreted the platformed monetized ritual in emotions to (de)code and (de)construct intimacy, and how users act on encountering the “unconcealed concealment” of mundane considerations, as well as the discontinuity of online/offline experiences of constructing intimacy. Reflecting on users’ choices and gender dynamics entangling the hybrid social orientations of materialism, individualism, and intervention of social institutions, this study underscores the fragile mechanism of digital dating and users’ trade-offs in the conundrum of heterosexual intimacy.